Expression and Significance of TNF-α and NF-κB/p65 in Cutaneous Lichen Planus - Chen JF; Zhang XM; Sanjel K; Zhang J; Ma C (Dove Medical Press, 2022)
Jun Fang Chen,1 Xue Mei Zhang,1,2 Kiran Sanjel,1,2 Juan Zhang,2 Cong Ma1 1The Dermatology and Venereology Department, The Affiliated Hospital of Inner Mongolia Minzu University, Tongliao, People's Republic of China; 2Clinical Medical School, Inner Mongolia Minzu University, Tongliao, People's Republic of ChinaCorrespondence: Xue Mei Zhang, The Dermatology and Venereology Department, The Affiliated Hospital of Inner Mongolia Minzu University, Tongliao, Inner Mongolia, 028000, People's Republic of China, Tel +8618504757225, Email tongliaozhangxuemei@126.comPurpose: The purpose of this study was to explore the expression of TNF-α and NF-κB/p65 in Lichen planus skin lesions and their correlation with the pathogenesis of Lichen planus.Patients and Methods: The case group consisted of 30 individuals diagnosed with LP based on clinical and histopathologic examination. The control group consisted of 10 individuals from an Orthopedic Department with normal skin. TNF-α and NF-κB/p65 expression in skin tissue samples was detected by immunohistochemistry.Results: The immunohistochemical results showed that TNF-α and NF-κB/p65 expression levels were significantly higher in LP skin lesions than normal skin tissues (P ≤ 0.05). Positive TNF-α staining mainly occurred in the cytoplasm of keratinocytes of the stratum granulosum, stratum spinosum, and stratum basale in the epidermis and lymphocytes in the superficial dermis. Positive NF-κB/p65 staining mainly occurred in the nucleus and cytoplasm of keratinocytes of the stratum spinosum and stratum basale in the epidermis and lymphocytes in the superficial dermis.Conclusion: TNF-α and NF-κB/p65 are overexpressed in cutaneous LP. The two are positively correlated in LP, suggesting that they both play essential roles in the pathogenesis of LP.Keywords: lichen planus, TNF-α, NF-κB/p65, staining, immunohistochemistry